Silhouette Functions of Short-Run Cost Behavior - Cooper, W. W.; Charnes, A. (Quarterly Journal of Economics, 1954)
I. Introduction, 131. — II. Scope of the model, 132. — III. Mathematical statement of the model, 134. — IV. Profit maximization, 140. — V. Cost-quantity silhouettes, 145.